2021
DOI: 10.1097/md.0000000000025091
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gut microbiota between allergic rhinitis, atopic dermatitis, and skin urticaria

Abstract: Introduction. Several forms of allergy have been clinically presented, including, among others, atopic dermatitis (eczema), urticaria (hives), and allergic rhinitis (rhinitis). As their detailed pathogenesis continues to be researched, we aimed in the current study to compare gut microbiota differences between eczema, hives, and rhinitis patients. Methods. We enrolled 19 eczemas, nine hives, and 11 allergic rhinitis patients in this study. Fecal samples were examined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In general, low richness and diversity of the gut microbiota have been linked to the development of allergic diseases. Recently, epidemiological studies have provided evidence for a possible relationship between gut microbiota dysbiosis and the risk of AR ( Chua et al, 2018 ; Su et al, 2021 ; Zhou et al, 2021 ). In addition, numerous studies have reported perturbations in the balance of gut microbiota are correlated with the development and progression of allergic and airway hyperresponsiveness diseases ( Cait et al, 2018 ; Langan et al, 2020 ; Zhang et al, 2021 ; Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, low richness and diversity of the gut microbiota have been linked to the development of allergic diseases. Recently, epidemiological studies have provided evidence for a possible relationship between gut microbiota dysbiosis and the risk of AR ( Chua et al, 2018 ; Su et al, 2021 ; Zhou et al, 2021 ). In addition, numerous studies have reported perturbations in the balance of gut microbiota are correlated with the development and progression of allergic and airway hyperresponsiveness diseases ( Cait et al, 2018 ; Langan et al, 2020 ; Zhang et al, 2021 ; Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of experimental technologies, 16S ribosomal RNA (rRNA) gene sequencing has been applied as a standard method to illustrate a more comprehensive picture of the intestinal microbiome. Since 2019, several studies have begun to report alterations in the gut microbiome of patients with CSU using this method; however, the research findings were not consistent with each other and were limited by their small sample sizes (9,10). In 2020, a combinational analysis incorporating gut microbiome data and serum metabolome data revealed a potential role of gut microbiota-associated alterations in unsaturated fatty acids and the butanoate metabolism pathway in the pathogenesis of CSU (11).…”
Section: Introductionmentioning
confidence: 99%
“…Infants at high risk of allergic disease (n=98) Australia; 2012 Gut microbial diversity was lower in infants with eczema compared to infants without eczema(48) Patients with AD (n=90), healthy control subjects (n=42) Korea; 2016 The proportion of Faecalibacterium prausnitzii was increased in patients with AD (49)Healthy infants (n=66), infants with AD (n=63) Korea; 2018 Bacterial cell amounts were lower and the relative abundances of Akkermansia muciniphila, Ruminococcus gnavus, and Lachnospiraceae bacterium 2_1_58FAA were decreased in infants with AD than in Clostridium difficile was associated with AD, and fewer Lactobacillus and more bifidobacterial in patients with AD(51) Patients with AD (n=44), healthy control subjects (n=49) China; 2021 Alpha diversity decreased in patients with AD than healthy subjects. Blautia, Parabacteroides, Bacteroides ovatus, Porphyromonadaceae, and Bacteroides uniformis were increased but Clostridium and Prevotella stercorea were reduced in patients with AD (52) Patients with AD (n=19), other allergic diseases patients (n=20) China; 2021The relative abundances of Bacteroidetes, Bacteroidales, Bacteroidia, Romboutsia, and Sutterella were significantly increased in patients with eczema(53) …”
mentioning
confidence: 99%